2015
DOI: 10.1155/2015/251937
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of a Diffusive Nutrient-Algae Model Based upon the Sanyang Wetland

Abstract: The stability and spatiotemporal dynamics of a diffusive nutrient-algae model are investigated mathematically and numerically. Mathematical theoretical studies have considered the positivity and boundedness of the solution and the existence, local stability, and global stability of equilibria. Turing instability has also been studied. Furthermore, a series of numerical simulations was performed and a complex Turing pattern found. These results indicate that the nutrient input rate has an important influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Their results indicate that the underlying mechanism ensures that the toxic phytoplankton group does not drive the zooplankton population toward extinction. For some recent results on the topic, we refer the reader to Javidi and Nyamoradi (2014), Wang et al (2014), Rehim et al (2015) and Wang et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicate that the underlying mechanism ensures that the toxic phytoplankton group does not drive the zooplankton population toward extinction. For some recent results on the topic, we refer the reader to Javidi and Nyamoradi (2014), Wang et al (2014), Rehim et al (2015) and Wang et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [2015] developed a diffusive nutrient-algae model for modeling the Sanyang wetland, China and found that the nutrient input rate has an important influence on the density and spatial distribution of algae population. Small fishes provide the crucial food base for higher trophic levels such as wading birds .…”
Section: Introductionmentioning
confidence: 99%